Direct collaboration between hospitals and NGOs, an essential tool to reinforce linkage to care in people living with HIV - Teresa Aldámiz-Echevarria; Chiara Fanciulli; Mónica Lopez; Leire Perez; Francisco Tejerina; David Sanchez; Blanca Lodeiros; Juan Carlos López; Juan Berenguer; Jose Maria Bellon; Maria Ferris; Mario Blazquez; et al. (Scientific Reports)
Abstract With the aim of improving access and engagement to healthcare in people living with HIV (PLHIV), in 2022 Gregorio Marañón Hospital and the NGO COGAM developed a circuit for recruitment and referral to hospital. Program targeted PLHIV who were neither receiving antiretroviral treatment (ART) nor on medical follow-up (FU); but also, individuals at risk who underwent screening tests at the NGO and, if positive, were referred for confirmation. The result was an increase in annual new PLHIV seen in hospital by reaching a population who were, essentially, young men (94% male, median age 30 years), migrants (95%) with recent diagnosis of HIV (median 5 years) and who were recently arrived in Spain (median 5 months). Most of them hadn´t healthcare coverage (78%). In multivariate analysis, that included all PLHIV seen for the first time in the ID Unit between 2019 and 2022, lack of healthcare coverage was the only independent predictor of lost to FU that reached statistical significance (HR 5.19, CI 2.76–9.47). Furthermore, time from HIV diagnosis to ART initiating was shortened from 14 to 6 days without affecting linkage to care. Our conclusion is that collaboration with NGOs reinforce diagnosis, FU, and adherence to ART for PLHIV.